2018
DOI: 10.1111/codi.14002
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy in refractory perineal Crohn's disease: long‐term follow‐up

Abstract: Combined therapy with adipose-mesenchymal stem cells, platelet-rich plasma and endorectal advancement flaps yielded good results in patients with refractory Perineal Crohn's Disease. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…The main features found in the 13 included studies are detailed in Figures 2 and 3. Among these, one study is about luminal CD 28 and the other 12 about perianal fistulizing CD 6 , 7 , 11 , 12 , 15 , 16 , 18 , 24 , 25 , 26 , 27 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…The main features found in the 13 included studies are detailed in Figures 2 and 3. Among these, one study is about luminal CD 28 and the other 12 about perianal fistulizing CD 6 , 7 , 11 , 12 , 15 , 16 , 18 , 24 , 25 , 26 , 27 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Partial healing was defined as external fistula opening remaining but with decrease of > 50% in size. This study found complete healing in 10/11 patients’ fistulas and partial healing in 1/11[ 15 ]. Conclusions were made that excellent success rates can be made for fistulizing CD with a multi-approach treatment method including ASCs, platelet rich plasma, and endorectal advancement flaps.…”
Section: Allogeneic Adipose Tissue Derived Stem Cell Therapy Trialsmentioning
confidence: 97%
“…Wainstein et al[ 15 ] also published a single center prospective observational pilot study conducted between 2013-2016 and included nine patients. Two stages were included in this study which was (1) “examination under anesthesia, fistula mapping, drainage and seton placement” and (2) setons removed four to six weeks with subsequent debridement and ASC then injected with biological plug formation.…”
Section: Allogeneic Adipose Tissue Derived Stem Cell Therapy Trialsmentioning
confidence: 99%
“…Partial healing was defined as external fistula opening remaining but with a decrease of >50% in size. This trial found complete healing in 10/11 patients’ fistulas and 1/11 partial healing 45. The authors decided that excellent success rates can be made for fistulizing CD with a therapy method including alloASC, platelet-rich plasma, and endorectal advancement flaps.…”
Section: Stem Cell Therapy For Fistulizing Diseasementioning
confidence: 99%
“…Finally, Wainstein et al published a single-center prospective observational pilot study conducted during 2013–2016 including nine patients 45. Two stages were included in this trial which were 1) “examination under anesthesia, fistula mapping, drainage and seton placement” and 2) setons removed 4–6 weeks with subsequent debridement and ASC then injected with biological plug formation.…”
Section: Stem Cell Therapy For Fistulizing Diseasementioning
confidence: 99%